Solar combined cooling, heating and power systems based on hybrid PVT, PV or solar-thermal collectors for building applications - Herrando,M; Pantaleo,AM; Wang,K; Markides,CN (Renewable Energy, 2019)
A modelling methodology is developed and used to investigate the technoeconomic performance of solar combined cooling, heating and power (S-CCHP) systems based on hybrid PVT collectors. The building energy demands are inputs to a transient system model, which couples PVT solar-collectors via thermal-store to commercial absorption chillers. The real energy demands of the University Campus of Bari, investment costs, relevant electricity and gas prices are used to estimate payback-times. The results are compared to: evacuated tube collectors (ETCs) for heating and cooling provision; and a PV-system for electricity provision. A 1.68-MWp S-CCHP system can cover 20.9%, 55.1% and 16.3% of the space-heating, cooling and electrical demands of the Campus, respectively, with roof-space availability being a major limiting factor. The payback-time is 16.7 years, 2.7-times higher than that of a PV-system. The lack of electricity generation by the ETC-based system limits its profitability, and leads to 2.3-times longer payback-time. The environmental benefits arising from the system’s operation are evaluated. The S-CCHP system can displace 911 tonsCO2/year (16% and 1.4× times more than the PV-system and the ETC-based system, respectively). The influence of utility prices on the systems’ economics is analysed. It is found that the sensitivity to these prices is significant.